A study of dispersion behavior of graphene oxide in organic solvents: article - Dison, Michelle-Anne; Marpani, Fauziah (2017)
Graphene has attracted the scientific interest in recent years due to its unique physical and chemical properties. The two-dimensional graphene is a new material with many emerging applications, and studying its chemical and physical properties is an important goal. Graphene oxide dispersion in organic solvent is highly desirable because it may significantly facilitatae the practical use of the material. Covalent functionalization is one of the ways to achieve single layer of dispersion, however the presence of stabilizer made it less desirable. To expand GO processibility and future practical use, the behaviour of GO in different organic solvent were investigated. In this study, graphene oxide was prepared by modified Hummer’s method and the surface morphology of GO is examined using FESEM. The prepared GO powder was dispersed in three different solvents, namely, Water, N,N-dimethylformamide (DMF), and Dimethyl sulfoxide (DMSO). Ultrasonic bath was used to prepare the dispersion of GO in solvents and the effect of different sonication time on the dispersion behavior of GO was observed. UV-Vis was used to measure the absorbance of GO in the solvents. Homogeneous dispersion was found in solvent with longer sonication time, however, only DMF and Water showed stable dispersion after 1 week which indicated that DMF and Water can be used for dispersion formation and further processing of graphene.